COVID-19 Pandemic: Resilience Measures from Romanian SMEs.: Array - Bucăța, George; Popescu, Florin (EuroEconomica, 2021)
In business, a company's resilience is its ability to cope with a catastrophic event, such as an economic crisis, a financial crisis, or a pandemic. However, there is a lot of confusion in the business world about what resilience means, how it can be built or developed, and how it can be assesed, especially during a difficult time of crisis. In this article, we want to define the term resilience, but also the way companies fight, the crisis with psychological and business techniques in an increasingly competitive environment.